# Thread: [SOLVED] Help finishing my proof for: Prove that inf A = -sup(-A)

1. ## [SOLVED] Help finishing my proof for: Prove that inf A = -sup(-A)

Let A be a nonempty subset of R (the reals) and let -A = {-x : x in A}.
Prove that inf A = -sup (-A).

My work:

Proof: Let A be non empty subset of R and
-A = {-x : x in A}. If -x is in -A then
-x < sup (-A) by the definition of supremum. This implies x > -sup (-A), and so
-sup (-A) is a lower bound of A.

Now that I look back on my work so far, I think I am wrong in assuming right away that a supremum exists. Do I have to first prove the existence of a supremum than show it is equal to the infimum? I am really stuck here.
Any help is greatly appreciated. Thank you for your time!

2. Originally Posted by ilikedmath
Let A be a nonempty subset of R (the reals) and let -A = {-x : x in A}.
Prove that inf A = -sup (-A).

My work:

Proof: Let A be non empty subset of R and
-A = {-x : x in A}. If -x is in -A then
-x < sup (-A) by the definition of supremum. This implies x > -sup (-A), and so
-sup (-A) is a lower bound of A.

your work is incomplete. showing it is a lower bound is not enough. you need to show it is the greatest lower bound. there are ways to do that elegantly. i will use the fact that $x \le y \text{ and } y \le x \implies x = y$ for $x,y \in \mathbb{R}$.

Let $A$ and $-A$ be as defined. By the definition of infimum, we have that $\inf A \le x$ for all $x \in A$. so that $- \inf A \ge -x$ for all $-x \in -A$. but that means $- \inf A$ is an upper bound for $-A$. thus, since the supremum is the least upper bound, we must have $- \inf A \ge \sup (-A)$ ........(1)

Also, $\sup (-A) \ge -x$ for all $-x \in -A$ by the definition of supremum. but that means $- \sup (-A) \le x$ for all $x \in A$, so that $- \sup (-A)$ is a lower bound for the set $A$. since the infimum is the greatest lower bound, we must have that $- \sup (-A) \le \inf A \implies \sup (-A) \ge - \inf A$ ...........(2)

By (1) and (2) we have $- \inf A = \sup (-A)$, as desired

Now that I look back on my work so far, I think I am wrong in assuming right away that a supremum exists. Do I have to first prove the existence of a supremum than show it is equal to the infimum? I am really stuck here.
Any help is greatly appreciated. Thank you for your time!
yes, we can assume the supremum and infimum exist. they are $\infty$ and $- \infty$ in the extreme cases

3. ## thanks!

thanks for the help!